The Factors Effecting Fund Size In the Pakistani industry : Factors Effecting Fund Size In the Pakistani industry (KASBIT Business Journal, 2024)
In recent years, the Pakistani asset management sector has experienced remarkable growth, necessitating an examination of factors impacting fund size. This study investigates the influence of risk-adjusted return (RAR), management structure (MS), expense ratio (EXP), and net asset value (NAV) on assets under management (AUM) within Pakistan. Utilizing five years of data from six prominent Asset Management Companies, our analysis reveals significant relationships. We find that a robust management structure inversely correlates with AUM, underscoring the importance of effective leadership. Moreover, lower expense ratios are associated with higher AUM growth, emphasizing the critical role of cost efficiency in attracting investor capital. While higher NAV values marginally correlate with larger AUM, superior risk adjusted returns significantly drive increased investor interest and capital inflows. Leveraging E-Views software, our findings offer actionable insights for asset managers, investors, and regulators, guiding strategic decisions and enhancing industry performance
Keywords: Asset Management, Fund Size, Risk-Adjusted Return, Management Structure, Expense Ratio, Net Asset Value, Assets Under Management, Pakistan.